(untitled) (Journal of Oriental Studies, 2018)
This article analyzes the national-cultural aspect of the number «two» in the Chinese linguoculture by comparative analysis in Kazakh language, as well as the national outlook and similarity in cultures of both countries. Also, some of the known linguistic scientists and Russian sinologists give their determinations to the number «two». There are many examples of the number «two» concerning phraseological expressions and equations related to the various etiquette units of the modern Chinese people’s ethnoculture.